Ileal tuberculosis presenting with bleeding per rectum followed by perforation peritonitis: A rare presentation (Indian Journal of Case Reports, 2017)
Here, I present a rare case of ileal tuberculosis who was admitted with bleeding per rectum associated with fever for 4?5 days. His Widal test was positive so was treated in the lines of enteric fever, but subsequently patient developed perforation peritonitis. On exploratory laparotomy, the whole abdominal cavity was filled with hemorrhagic fluid along with perforation at ileal segment around half a feet proximal to ileocecal junction and site was filled with blood clot. Ileostomy was performed but the patient had persistent fever beside higher antibiotics. Latter chest X?ray of the patient showed pleural effusion on the left side, and pleural fluid analysis showed the evidence of tuberculosis. Histopathological report of ileal segment confirmed the diagnosis of tuberculosis. The patient is responding well to antituberculosis treatment and now waiting for ileostomy closure.